1996
DOI: 10.1007/bf02110668
|View full text |Cite
|
Sign up to set email alerts
|

Childhood factors and war zone stress in chronic PTSD

Abstract: This study assessed the predictive validity of combat factors and selected premilitary variables (i.e., childhood physical abuse, substance abuse in the family of origin, or being raised in a nonadaptive or noncohesive family) on posttraumatic stress disorder (PTSD) group membership. In addition, it assessed the correlation of combat exposure and selected premilitary variables with the severity of PTSD symptomology. Ninety-three male Vietnam combat veterans with PTSD were compared to 82 male Vietnam combat vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Research also should be devoted to examining possible factors that predict whether veterans will be at risk for experiencing subthreshold versus diagnostic levels of PTSD symptoms following combat. Level of combat exposure did not distinguish between veterans reporting subthreshold-PTSD and PTSD in the current study; however, other factors may include pre-existing trauma exposure (see Donovan, Padin-Rivera, Dowd, & Blake, 1996) or intelligence level (see Macklin et al, 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Research also should be devoted to examining possible factors that predict whether veterans will be at risk for experiencing subthreshold versus diagnostic levels of PTSD symptoms following combat. Level of combat exposure did not distinguish between veterans reporting subthreshold-PTSD and PTSD in the current study; however, other factors may include pre-existing trauma exposure (see Donovan, Padin-Rivera, Dowd, & Blake, 1996) or intelligence level (see Macklin et al, 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Because PTSD is influenced by environmental factors that predate exposure to a focal traumatic event, epigenetic mechanisms may be highly relevant. There is good evidence in the animal literature that DNA methylation is a mechanism operative in programming the activity of genes regulating HPA activity by early life events (i.e., differences in maternal care) [57][58][59][60][61][62] that parallel observations that early life events are associated both with the development of PTSD and the HPA axis alterations described in this condition [63][64][65][66][67][68][69]. Such changes result in permanent changes in hippocampal GR expression and HPA function and provide a clear molecular link between early environment and gene expression and function.…”
Section: Environmental Exposures Can Results In Epigenetic Alterationsmentioning
confidence: 99%
“…In addition, longer or more intensive trauma exposure is associated with more severe symptoms (Vernberg & Varela, 2001). For instance, Vietnam veterans who reported childhood physical abuse had higher rates of combat-related PTSD (Bremner et al, 1995;Donovan, Padin-Rivera, Dowd, & Blake, 1996). Bremner et al (1995) suggested that living in a chaotic, stressful environment in childhood increases one's risk of developing PTSD when exposed to severe trauma later in life.…”
Section: Childhood Trauma Exposurementioning
confidence: 96%